2021
DOI: 10.1177/20503121211056216
|View full text |Cite
|
Sign up to set email alerts
|

The status of serum cortisol before and after treatment of schizophrenia and its correlation to disease severity and improvement: A longitudinal study

Abstract: Background: Hypothalamic–pituitary–adrenal axis functioning, with cortisol as its major output hormone, has been presumed to play a key role in the development of psychopathology of schizophrenia. Objective: We examined the association of serum cortisol with disease severity and improvement in schizophrenia patients in Jimma, Ethiopia. Method: A total of 34 newly diagnosed schizophrenics were included in this study. Data on demographic, behavioral, clinical state, serum cholesterol level, and antipsychotic usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…In the Woldesenbet et al study, at baseline, no association was observed between serum cortisol levels in schizophrenia patients and PANSS positive and negative sub-scores. However, after treatment with antipsychotics, serum cortisol levels showed a strong association with PANSS positive and negative subscores (31). In the present study, no association was observed between serum cortisol levels and PANSS scores.…”
Section: Relationship Between Demographic Variables and Cortisol And ...contrasting
confidence: 80%
See 1 more Smart Citation
“…In the Woldesenbet et al study, at baseline, no association was observed between serum cortisol levels in schizophrenia patients and PANSS positive and negative sub-scores. However, after treatment with antipsychotics, serum cortisol levels showed a strong association with PANSS positive and negative subscores (31). In the present study, no association was observed between serum cortisol levels and PANSS scores.…”
Section: Relationship Between Demographic Variables and Cortisol And ...contrasting
confidence: 80%
“…According to the results of Woldesenbet et al, serum cortisol levels were signi cantly lower in schizophrenia patients after treatment with antipsychotics compared to their baseline values. However, due to limitations related to assessing the effect of medication, it is essential to approach these ndings cautiously (31). Yildirim et al evaluated serum cortisol levels in patients with schizophrenia, comparing them with control relatives and control volunteers.…”
Section: Relationship Between Demographic Variables and Cortisol And ...mentioning
confidence: 99%
“…Treatment with various antipsychotic drugs (risperidone, haloperidol, chlorpromazine, olanzapine) was used in patients newly diagnosed with schizophrenia for 8 weeks. Post-treatment serum cortisol concentrations were significantly lower than those at the baseline [84].…”
Section: Long-term Treatmentsmentioning
confidence: 55%
“…A similarly low cortisol value was recorded in a patient after aripiprazole, but during polytherapy with lamotrigine and sertraline. Likewise, Woldesenbent et al, in their study on the impact of antipsychotic treatment on the cortisol level in a group of patients with newly diagnosed schizophrenia, observed a significant decrease the initial blood cortisol concentration after treatment [32]. Glutamate, the anionic form of glutamic acid, is the main excitatory neurotransmitter in the brain, the homeostasis of which is regulated by glutamate transporters [33].…”
Section: Distributions Of Clinical Parameters By Groupsmentioning
confidence: 98%